2004
DOI: 10.2322/tjsass.47.189
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ignition of n-Alkane Droplets with Various Volatility

Abstract: Ignition delays of a cool flame ( 1 ) and a hot flame ( t ) were measured experimentally for single n-decane, n-dodecane, n-tetradecane and n-hexadecane droplets, which have similar volatilities to common commercial hydrocarbon fuels, in hot air. Droplet diameter was 0.7 mm. Ambient pressure was 0.3 and 1.0 MPa. Ambient temperature was 550 K to 1000 K. Results show the similarity of the examined fuels in terms of reactivity of the low-and high-temperature reactions. Values of 1 and t were longer for fuels with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tanabe et al reported that hydrocarbon droplets such as ndodecane also shows these phenomena [9], [10] . Additionally, Moriue measured cool flame and hot flame ignition of various alkane droplets, and showed that cool flame ignition delay mainly depends on volatility of fuels [11] . On the other hand, characteristics of spray combustion is largely influenced by the interaction between droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Tanabe et al reported that hydrocarbon droplets such as ndodecane also shows these phenomena [9], [10] . Additionally, Moriue measured cool flame and hot flame ignition of various alkane droplets, and showed that cool flame ignition delay mainly depends on volatility of fuels [11] . On the other hand, characteristics of spray combustion is largely influenced by the interaction between droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Tanabe et al 2) revealed the role of cool flame in the two-stage ignition process (cool-and hot-flame appearances) of n-alkane droplets experimentally through interferometry. Moriue et al 3) measured ignition delays of cool flame and hot flame for many kinds of n-alkane droplets in the wide ranges of ambient temperature and pressure. Schnaubelt et al 4) compared the experimental results in microgravity, where the effect of buoyancy is strongly reduced, with a numerical model with a detailed chemical reaction model, and verified the model quantitatively.…”
Section: Introductionmentioning
confidence: 99%